EFEKTIFITAS COUNTER PRESSURE TERHADAP NYERI PERSALINAN PADA IBU BERSALIN KALA I FASE AKTIF DI WILAYAH KERJA PUSKESMAS NOJONG RAWALUMBU KOTA BEKASI: THE EFFECTIVENESS OF COUNTER PRESSURE ON LABOR PAIN IN MOTHERS IN ACTIVE PHASE I PAGE IN THE WORK AREA OF THE PUSKESMAS NOJONG RAWALUMBU, BEKASI CITY - Intan Baiduri; Putri Azzahroh; Triana Indrayani (Jurnal Penelitian dan Kajian Ilmiah Kesehatan Politeknik Medica Farma Husada Mataram, 2021)
Labor pain can affect uterine contractions through the secretion of catecholamine and cortisol levels which increase the activity of the sympathetic nervous system, changes in blood pressure, heart rate, respiration and consequently affects the length of labor. Pain can also cause uncoordinated uterine activity which will result in prolonged labor. Counter Pressure Massage is a non-pharmacologic method that can help reduce labor pain in mothers in the active phase of the first stage of labor. This study uses a pre-experimental research method with a one group pretest posttest research design. Samples were taken using a purposive sampling technique, as many as 20 mothers gave birth. The instruments used in this study were SOP sheets (Standard Operating Procedures), and pre and post observation sheets for giving counter pressure massage to mothers in active phase I labor. The data were analyzed using the Wilcoxon signed ranks test. Prior to the Counter Pressure Massage, most of the respondents were on a scale of 4-6 (moderate pain) as many as 11 people (55%) and on a scale of 7-9 (severe pain) as many as 9 people (45%). After doing a Counter Pressure Massage, some respondents were on a scale of 1-3 (mild pain) as many as 10 people (50%) and some on a scale of 4-6 (moderate pain) as many as 10 people. The results showed that there was a significant difference in the respondents' pain scores before and after being given Counter Pressure Massage with the Wilcoxon test p = 0.000 (p < 0.05). ConclusionCounter Pressure Massage is effective in reducing labor pain in active phase I maternity mothers in the Work Area of ??Bojong Rawalumbu Health Center, Bekasi City.